2008
DOI: 10.1080/17518420701780115
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of challenges faced by parents of children with ABI with and without access to third party funding

Abstract: Although results indicated significant psychological distress and depressive symptoms for both groups, parents in both groups reported high availability of and satisfaction with services, although they used very few services. Implications for clinical services are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…A total of 28 articles met the inclusion criteria and were examined in-depth with data tabulated. Three qualitative systematic reviews (4,7,21), one scoping review (18) and two practice recommendation articles (22,23), (Table 3) and 22 original research studies were identified (Table 4) (6,10,11,17,19,20,(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 28 articles met the inclusion criteria and were examined in-depth with data tabulated. Three qualitative systematic reviews (4,7,21), one scoping review (18) and two practice recommendation articles (22,23), (Table 3) and 22 original research studies were identified (Table 4) (6,10,11,17,19,20,(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39).…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen articles focussed specifically on the needs of CYP with TBI and their families (6, 10, 11, 17, 19, 20, 25-27, 30, 32-35, 38), three specifically on the needs of CYP with brain tumours (24,29,36), one on the needs of CYP critical care survivors, including CYP with ABI (31) and three on the needs of CYP with ABI (TBI and NTBI) (28,37,39).…”
Section: Research Studiesmentioning
confidence: 99%
“…Our study findings about the benefits of support groups with others going through similar experiences reinforce the work of other researchers who reported that access and participation in support groups helped to increase caregivers' ability to understand themselves and others, to talk and be listened to without judgment, to put their problems into perspective, and to make use of the group to provide an outlet for stress relief. (Jackson et al, 2008;Lefley, 1997;Lovenfosse & Viney, 1999;Nuutila & Salantera, 2006;Rosenwald & Bronstein, 2008;Vilela, Phillips, and Minnes , 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The Canadian healthcare system has a similar socialized funding base, with private funding provided to those injured in motor vehicle accidents. A follow-up study of children who had sustained TBIs up to 5 years earlier found that those who had access to private funding showed better engagement in daily activities and that their parents felt more supported [33]. It is likely that this is also the case in Victoria, and that access to funding has less impact during the inpatient phase of care, but impacts on services and supports after discharge.…”
Section: Type Of Fundingmentioning
confidence: 85%